Micromorphology to study of earthen built heritage - Mateu Sagues, Marta (Restauro Compás y Canto S.A., 2021)
The earthen architecture heritage of past societies is studied by archaeology, using different techniques. Micromorphology allows to define the composition of the building material and the construction techniques, by analyzing thin sections of oriented samples with a petrographic microscope. This article describes the method and presents examples of mudbricks, cob walls, floors, and roofs from Iberian and Mesoamerican sites. Mineralogical composition and the presence of specific soil formation features allow to define from where the building sediments were extracted and how different soils may have been mixed, while the form in which minerals are aligned and the type, size and form of pores reveal the amount of water added to the mix, and the direction and intensity of compaction. Thus, it is possible to differentiate mudbricks from floors and facings, cob from rammed earth. This method helps to validate the interpretation of construction techniques derived from archaeological excavations and provides crucial information for the adequate preservation of this heritage.